Post occupancy evaluation measures of green interiors tools Energy Efficiency (EE) core criteria - Yaman, Rostam; Abdullah, Jamalunlaili; Adnan, Hamimah; Ismail, Farrah Zuhaira; Ahmad, Noraini (IOP Publishing Ltd, 2019)
Interior spaces sustainable rating system in Malaysian is rather new. Even though Green Building Index Interior Tools (GBI-IT) has been developed and implemented but there is a lack of post-occupancy evaluation being conducted in assessing the sustainability level of the certified project, particularly on the Space Energy Intensity (SEI). Thus, embarking on the research problem whether the certified interior space sustainable level is according to the pre-occupancy scoring benchmark as a vision by the designers upon occupancy, particularly on Energy Efficiency (EE). The research objective is to examine the SEI, to identify similarities and discrepancies of SEI upon pre-occupancy evaluation and post-occupancy evaluation and to assess the key EE sub-criteria that affect Space Energy Intensity (SEI) and to improve continuing sustainable EE upon post-occupancy. The Space Energy Intensity equation approach and implementation method are used in this research to measure total space energy consumption per year/interior space area. The research design will be formulated into three key stages, which are; 1. Content analysis of GBI Interior Tools EE core criteria; 2. Comparative data analysis between pre-occupancy and post-occupancy EE sub-criteria scoring and; 3. Assessment of key EE sub-criteria that affect Space Energy Intensity (SEI) and to improve continuing sustainable EE upon post-occupancy. The findings for the research problem based on Space Energy Intensity (SEI) on-site measure from the case study will improve sustainability practice and continuing a sustainable agenda, particularly on EE. The study outcome will facilitate and enhance the current and future sustainable approach in interior SEI.